Public management innovations in the United Arab Emirates: rationales, trends and outcomes. Issue 4 (7th October 2019) - Khalid, Saba; Sarker, Abu Elias
Abstract : Purpose: The purpose of this paper is to analyze the rationales for, the trends and the impacts of innovations in the public management system of the United Arab Emirates (UAE). Design/methodology/approach: This study has adopted an interpretative and exploratory approach. To this end, extensive reviews have been made of government documents, reports of international organizations and relevant academic research articles. Findings: The findings show that the UAE Government has embarked on a massive innovation program to bring dynamism and to feed the requirements of the UAE Vision 2021. As pressured by both external and internal forces, the directions of innovations in the UAE public management system correspond to the global trends. The results of innovations are positive in terms of the enhancement of efficiency, effectiveness, citizens' satisfaction and citizens' trust in public services. Originality/value: This paper links theoretical insights from different sources to analyze the dynamics of public management innovations in the UAE which will be helpful for further comprehensive empirical research in the future.